The Role of Halal Certification and Online Advertising Strategies in Shaping Consumer Demand in the Digitalization Era - Siti Aminah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
In the rapidly evolving era of digitalization, the roles of halal certification and digital marketing strategies are increasingly influencing consumer behavior and their demands for products and services. This article aims to unveil the pivotal roles of halal certification and digital marketing strategies in shaping consumer preferences in the digitalization era. Halal certification has become a crucial factor in meeting the needs of consumers who are becoming more conscious of religious and health aspects in their products and services. On the other hand, changes in technology and consumer behavior have opened new doors for digital marketing, especially through online platforms and social media. This article dissects how halal certification impacts consumer purchasing decisions in the digital environment and how digital marketing strategies can be employed to enhance awareness and understanding of halal products. By analyzing the impact of the combination of these two factors, this article provides deep insights into how the roles and interactions between halal certification and digital marketing strategies affect consumer demands in the current digitalization era. The findings of this research have significant implications for companies aiming to meet the diverse and discerning demands of consumers. With a better understanding of how halal certification and digital marketing can work together, companies can design more effective strategies to reach and retain consumer preferences in a competitive and ever-changing business environment.